Daniel Johnston : A Portrait of the Artist as a Potter in North Carolina - Glassie, Henry, 1941- (Book collections on Project MUSE., 2020)
"Daniel Johnston, raised on a farm in Randolph County, returned from Thailand with a new way to make monumental pots. Back home in North Carolina, he built a log shop and a whale of a kiln for wood-firing. Then he set out to create beautiful pots, grand in scale, graceful in form, and burned bright in a blend of ash and salt. With mastery achieved and apprentices to teach, Daniel Johnston turned his brain to massive installations. First, he made a hundred large jars and lined them along the rough road that runs past his shop and kiln. Next, he arranged curving clusters of big pots inside pine frames, slatted like corn cribs, to separate them from the slick interiors of four fine galleries in succession. Then, in concluding the second phase of his professional career, Daniel Johnston built an open-air installation on the grounds around the North Carolina Museum of Art, where 178 handmade, wood-fired columns march across a slope in a straight line, 350 feet in length, that dips and lifts with the heave while the tops of the pots maintain a level horizon. In 2000, when he was still Mark Hewitt's apprentice, Daniel Johnston met Henry Glassie, who has done fieldwork on ceramic traditions in the United States, Brazil, Italy, Turkey, Bangladesh, China, and Japan. Over the years, during a steady stream of intimate interviews, Glassie gathered the understanding that enabled him to compose this portrait of Daniel Johnston, a young artist who makes great pots in the eastern Piedmont of North Carolina"--